PERANCANGAN REPOSITORI ARSIP VIDEO KARYA SENI ISI SURAKARTA - Wahyu Widyasih (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
ABSTRACT This study seeks to develop a design for managing video archives of ISI Surakarta's artworks so that it can be used as a source of learning, research, work, information and policy making references. The research has been conducted qualitatively by identifying, observing, mapping, and compiling designs. The object of the research is the video archive of works of art at ISI Surakarta, both final projects, research results, and community service results. The purpose of the research is to formulate a design for managing video archives of artwork at ISI Surakarta according to archival principles so that it is informative, safe, and easily accessible to users. An archive repository is a design that can be set up for managing video archives of artwork. Repositories have the advantage of making it easier for users to access open archives of artwork videos. The design of the artwork video archive repository as a video art archive management system at ISI Surakarta is divided into 3 stages including (1) content identification, metadata, and classification codes; (2) development of a video archive repository of artworks which includes archival policies, interface design, quality control, procedure manuals, and copyrights. (3) Arrangement of video archives of artworks in the repository with stages (a) identification of video archives of artworks which include the process of collecting physical archives (technical handling) and data collection of archive information (intellectual handling); (b) compiling an archive classification scheme; (c) creation of a video archive description of artwork; (d) maneuvering the video archive of the artwork through the stages of assigning a definitive number, maneuvering the description card, and maneuvering the video archive of the artwork; and (e) preparation of a retrieval scheme through a video archive list of works of art.